Risk, Characteristics and Biomarkers of Cytokine Release Syndrome in Patients with Relapsed/Refractory AML or MDS Treated with CD3xCD123 Bispecific Antibody APVO436 - Fatih M. Uckun (MDPI AG, 2021)
We evaluate the risk, characteristics and biomarkers of treatment-emergent cytokine release syndrome (CRS) in patients with relapsed/refractory acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) who received APVO436 during the dose-escalation phase of a Phase 1B study (ClinicalTrials.gov, identifier: NCT03647800). Of four patients who developed Grade ≥ 3 CRS, two received steroid prophylaxis. The dose level, gender, race, obesity, or baseline hematologic parameters in peripheral blood did not predict the risk of CRS. Patients with a higher leukemia burden as determined by a higher total WBC, higher percentage of blasts in bone marrow, or higher percentage of blasts in peripheral blood (by hematopathology or immunophenotyping) did not have a higher incidence of CRS. There was an age difference between patients who did versus patients who did not develop CRS (72.9 ± 1.6 years (Median 73.5 years) vs. 63.3 ± 2.3 years (Median: 65.0 years), which was borderline significant (p = 0.04). Premedication with steroids did not eliminate the risk of CRS. Cytokine profiling in patients who developed CRS after APVO436 infusion indicates that the predominant cytokine in this inflammatory cytokine response was IL-6. APVO436-associated CRS was generally manageable with tocilizumab with or without dexamethasone. Notably, the development of CRS after APVO436 therapy did not appear to be associated with a response. The prolonged stabilization of disease, partial remissions and complete remissions were achieved in both patients who experienced CRS, as well as patients who did not experience CRS after APVO436 infusions.